Student Engagement Variables and First Year Undergraduate Retention Rate in University of Uyo, Akwa Ibom State, Nigeria - Iroegbu, Ekaette Emenike; Agboola, Bolapeju M. (American Journal of Education and Learning, 2019)
The study examined Student Engagement Variables and First Year Undergraduate Retention Rate in University of Uyo, Akwa Ibom State, Nigeria. Five research questions and four hypotheses guided the study. The descriptive survey research design was used for the study. The population comprised 3,447 first year undergraduates from University of Uyo. Purposive and simple random sampling techniques were used to select 548 first year undergraduates studying four-year courses in University of Uyo. Two instruments titled; “Student Engagement Questionnaire (SEQ)” and a documentary analysis checklist were used for data collection. The reliability co-efficient of SEQ was determined using the Cronbach Alpha Analysis and a reliability index of 0.82 was obtained. Mean, coefficient of R value and R2 of Simple Linear Regression were used to answer research questions while F ratio of Simple Linear Regression Analysis was used to test the null hypotheses at 0.05 alpha level. The findings of the study revealed that student engagement variables of active learning, student – faculty interaction, teaching strategies and co-curricular activities significantly predicts first year undergraduate retention rate in University of Uyo, Akwa Ibom State. It was therefore concluded that, student engagement variables relate significantly to first year undergraduate retention rate in University of Uyo. Based on the findings of this study, it is therefore recommended amongst others that, faculties should create a healthy learning atmosphere and positive student - faculty interactions in order to guarantee student retention.